2003
DOI: 10.1046/j.1365-2648.2003.02601.x
|View full text |Cite
|
Sign up to set email alerts
|

Space and place in the construction and performance of gendered nursing identities

Abstract: Three aspects of the relationship between nurse and hospital spaces are considered. First, the degree of access that nurses have to the different hospital spaces is limited, and many are confined to the wards in which they work. The high proportion of female nurses working on wards means that there are marked gender differences in access to hospital spaces. There are also marked professional differences when nurses are compared to doctors who have much greater freedom to roam and there are differences in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
91
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(98 citation statements)
references
References 13 publications
(13 reference statements)
5
91
0
2
Order By: Relevance
“…One reason given for this feeling of control is that the woman has the higher status of 'resident' at home and the midwife is constructed as a 'visitor', whereas in hospital these roles are reversed. 37 Following this, Gilmour 38 argued that transforming hospital spaces so they are more home-like challenges the dominance of biomedical values, a claim disputed by Fannin,39 who argued that it is presumptive to assume that making a hospital space more like a home will in itself fend off the controlling influence of biomedicine. Others have also been critical of the assumptions that underlie the discourses of pro-home birth academics and activists.…”
Section: Development Of Birth Centresmentioning
confidence: 99%
“…One reason given for this feeling of control is that the woman has the higher status of 'resident' at home and the midwife is constructed as a 'visitor', whereas in hospital these roles are reversed. 37 Following this, Gilmour 38 argued that transforming hospital spaces so they are more home-like challenges the dominance of biomedical values, a claim disputed by Fannin,39 who argued that it is presumptive to assume that making a hospital space more like a home will in itself fend off the controlling influence of biomedicine. Others have also been critical of the assumptions that underlie the discourses of pro-home birth academics and activists.…”
Section: Development Of Birth Centresmentioning
confidence: 99%
“…Health care practitioners also, wittingly or otherwise, discourage interactions and requests for help from patients through their body language (Halford and Leonard 2003). Practitioners of complementary and alternative medical (CAM) usually articulate a more equalitarian view of practitioner-patient relations than those in allopathic medicine (Oerton 2004, Sointu 2006), but it is not by chance that their health care practices do not generally require the infliction of pain or the immobilization of the patient, so that the micropolitics of their interactions rarely challenge the equalitarian ethos.…”
Section: The Power Relations Of Body Workmentioning
confidence: 99%
“…Shaw and Kitzinger (2005) and Davis-Floyd and Davis (1996) are among a number of writers who have suggested that women feel more in control of their birth at home or in home-like settings such as free-standing birth centres. One reason given for this feeling of control is that the woman has the higher status of 'resident' at home and the midwife is constructed as a 'visitor', whereas in hospital these roles are reversed (Halford and Leonard 2003). This writing also echoed the critical literature on residential care, where those in need of care attempt to live 'private lives in public places' (Willcocks et al 1986).…”
Section: The Literature On Place and Therapeutic Spacesmentioning
confidence: 99%